COUNSELING WITH VIDEO MEDIA TO IMPROVE CARING ATTITUDES IN NURSING STUDENTS - Putri, Prestasianita; Mardijanto, Said; Adelia Susanti, Ika (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Background: Caring is an important thing that must be owned by nurses to perform services to patients. Caring must be familiarized starting from educational programs or students. Objective: Increase attitude about caring for nursing students Methods: Using counseling by video method, which was done on 30 nursing students. Results: The results of caring attitudes from measurements before counseling with video media obtained an average score of 3.4 out of a total score of 5, after counseling with video media, which was 4.2 out of a maximum score of 5. Conclusion: Counseling with video media can improve the caring attitude of nursing students.